Single-center experience in the management of spontaneous isolated abdominal aortic dissection - Böckler, Dittmar; Bianchini Massoni, Claudio; Geisbüsch, Philipp; Hakimi, Maani; Tengg-Kobligk, Hendrik von; Hyhlik-Dürr, Alexander (Langenbeck's archives of surgery, 2016)
This study aims to report the management of patients with spontaneous isolated dissection of the abdominal aorta (sIAAD).
Published: 22 September 2015
Gesehen am 13.05.2020